OFR-40-78 An Investigation Of The Effects Of Hardened Washers On The Uniformity Of Roof Bolt Tension And Resulting Ground Control In An Underground Mine - R. S. Rosso (The National Institute for Occupational Safety and Health (NIOSH), 1977)
A program to investigate the effects of hardened washers on the uniformity of roof bolt tension and the resulting ground control in an underground mine was carried out. The complete roof bolt installation and roof bolt loads, mine convergence, and bed separation were monitored for a period of five months. The results show no evidence to support or refute the theory that mechanical roof bolts offer better support when they are installed with a high uniformity of tension. Also shown is the fact that if the bolts are installed with a maximum deviation from the mean torque of ±15% the addition of hardened washers significantly improved the uniformity of the installed tensions in the roof bolts.